Benefits of Digital Training Approaches on Non-Banking Economic Divisions in India - Palak Dev,; Sainger, Garima (Mercados y Negocios, 2025)
The current research examines the benefits of digital training approaches in non-banking economic divisions in India. The present study adopted quantitative analysis employing the SPSS version 23 software package. A structured questionnaire survey method is used to collect the data from employees working in the non-banking economic division, and a purposive sampling approach is used for analysis. The objective of the method is to collect data relating to employees' insights concerning adopting digital training. ANOVA, frequency, and regression tests are executed in research. The study's outcomes revealed the prevalence of digital training in non-banking institutions and the significance of online learning platforms in offering practical training to employees. Furthermore, the study also evaluates the impact of digital training approaches on employee performance in the organization. The study recommends implementing online learning platforms in non-banking financial institutions to accomplish organizational objectives.